Orientation Control of Molecularly Functionalized Surfaces Applied to the Simultaneous Alignment and Sorting of Carbon Nanotubes. Issue 9 (5th February 2018) - Selmani, Serxho; Schipper, Derek J.
Abstract: Self‐assembly has been relied upon for molecular alignment in many advanced technological applications. However, although effective, it is inherently limited in its capability for optimization. Despite the potential benefits, the seemingly fundamental strategy of external orientation control has yet to be realized. Herein we demonstrate an approach that allows control of the orientation of small molecules covalently bound to a surface. The method exploits an alignment relay technique, passing alignment information through a liquid‐crystal medium to small molecules to control surface functionalization events. The method is technically simple and can be carried out on a bench top without the need for specialized equipment. Moreover, we demonstrate the utility of the resulting surfaces to address two long‐standing problems in nanoscience: the sorting and alignment of single‐walled carbon nanotubes. This new method enabled significant alignment of the nanotubes as well as length and diameter sorting. Abstract : The ART of science : An alignment relay technique (ART) has been developed for the alignment of organic molecules covalently bound to a surface. The resulting functionalized surface was used to promote the simultaneous alignment and length and diameter sorting of single‐walled carbon nanotubes (see picture).